Optimal Strategies of Foreign Banks to Enter the Russian Market on The Example of Pingan Bank Co., Ltd. - Hui Ma; Timofey Mazurchuk (Communications of International Proceedings, 2021)
The international program is now very quickly covering its capabilities to introduce its banks, including in the Russian markets, and this can no longer be rebuffed. Because it is very convenient for users of their services, due to the fact that the range of services and consumer goods is increasing, as well as the choice between banks whose quality is better. Thus, in the process of competition, the cost of the goods decreases and the service becomes even better. There are a lot of foreign banks in Russia. As of April 01, 2020, 63 foreign banks out of 390 operated. More than half of these banks are from Europe, 17 banks are from Asia [5]. The banking sector in Russia is highly competitive. Therefore, foreign banks, especially from China strive to stand out and lead among competitors. Almost all foreign banks have identical tactics and strategies. These strategies target a similar demographic of banking consumers. By using a variety of strategies in the international marketplace, a financial institution can differentiate itself from its competitors by offering the latest technology to consumers in a variety of ways.
Keywords: banking; marketing; strategies; market; credit organizations; tactics; advertising.